Smart Water Dispenser Terintegrasi untuk Monitoring Konsumsi Air Minum Harian - Deni Ariyanto Abadi; Laurentius Kuncoro Probo Saputra; Gloria Virginia (STMIK Budi Darma, 2021)
Lack of water can cause serious health problems. In reality, some people do not know the amount of water they must drink daily. It's hard to find out the daily water intake needs because it is affected by a lot of things and it will be better to involve a nutritionist or health expert to get the best amount, which may require extra cost. To overcome these problems, it is necessary to have a system that is incorporated in an integrated system with the ability to calculate the ideal level of water needs for the body according to factors that affect the level of water needs and able to remind users to keep their daily needs. IoT-based smart water dispensers that can be integrated with android applications and cloud servers into a single system can be used to help solve these problems. The system has a knowledge base obtained from professionals to determine user water consumption. The system calculates the water consumption using the GPPAQ questioner and Estimated Energy Requirement (EER) formula. The base knowledge is implemented on Android applications, and this application can track the amount of water that has been consumed by the user. The test results show that the system can calculate the amount of water demand based on some factors such as the level of physical activity, age, and body weight. The water dispenser system has an accuracy of recording the amount of air released by 92.6%, so there is a difference in the calculation in the Android application to the amount of air that the user takes from the water dispenser